Income Mobility Comparisons and Equivalizing Transformations - Abatemarco, Antonio (Journal of Income Distribution®, 2004)
The existing literature on income mobility comparisons is strongly characterized by contrasting results and empirical puzzles. In this paper we focus on the role of the equivalizing transformation for the definition of complete mobility orderings. Two crucial considerations are involved. First, we suggest that a separating line should be drawn between measuring intra-generational income mobility and measuring socially relevant effects of intra-generational income mobility. Secondly, we observe that some of the normative issues entailed in the definition of efficient mobility indices should be opportunely revisited once the equivalizing transformation has been implemented, not before. In this scenario, the use of equivalent adults seems to be the more normatively efficient solution whenever income mobility orderings are investigated over heterogeneous societies. In particular, this result seems to be supported by the empirical investigation over eight countries and five waves (ECHP – PSID), that is, most of detected empirical puzzles in the existing literature disappear when the reference income unit consists of the equivalent adult.